A descriptive Study on the Students’ Perception towards Code-Switching Used by English Teachers in Teaching-Learning Process at SMK Negeri 1 Banyuwangi in Academic Year 2019/2020 - Jaenal Abidin; Wageyono; Wulan Wangi (LUNAR, 2021)
Language is primarily a speech. It is used in a society and it is a social event. People use a language for communication with each other. This research aimed to describe students’ perceptions toward code-switching used by English teacher, and the types of code-switching that used teacher in teaching-learning process. The research design was descriptive qualitative. The respondents were 36 students in SMK Negeri 1 Banyuwangi which determined by used purposive sampling. The data were taken by used documentation and questionnaire. The data from documentation used to analyze the types of code-switching. The data from questionnaire analyzed by using Likert scale. The data analysis was determined based on theory of interest with four indicators. They are effect of code-switching in rising their confidence, learning materials mastery, learning motivation, and interaction in teaching-learning process. The result of documentation show that there are three types of code switching that used by teacher in teaching-learning process. The percentage are tag code-switching (27,55%), inter sentential code-switching (43,87%), and intra sentential code-switching (28,57%). Analysis of questionnaire data showed that the index percentage of students’ perceptions toward code switching used by English teacher was 73% that consists of effect of code-switching in rising students’ confident 75%, analyzing learning materials mastery 77%, learning motivation 73%, and 69% interaction in teaching-learning process.